Context‐aware hybrid satellite‐terrestrial broadband access. (18th November 2018) - Ekmekcioglu, Erhan; Evans, Barry; Kondoz, Ahmet; Thompson, Paul; Ottavj, Luc; Gamberini, Fabrice; Watts, Simon
Summary: One of the key performance targets on the European Commission's Digital Agenda is to provide at least 30‐Mbit/s broadband coverage to all European households by 2020. The deployment of existing terrestrial technologies will not be able to satisfy the requirements in the most difficult‐to‐serve locations, either due to a lack of coverage in areas where the revenue potential for terrestrial service providers is too low or due to technological limitations that diminish the available throughput in rural environments. In this paper, we investigate a hybrid broadband system combining satellite and terrestrial access networks. The system design and the key building blocks of the intelligent routing entities (referred to as intelligent gateways) are presented. To justify the hybrid broadband system's performance subjectively, lab trials have been performed with an integrated multiple access network emulator and a variety of typical multimedia applications that have varying requirements. The results of the lab trials suggest that the quality of experience is consistently improved thanks to the utilisation of intelligent gateway devices, when compared with using a single access network at a time. Abstract : This study investigates a hybrid broadband system combining satellite and terrestrial access networks and deploying an intelligent routing technology. We outline the details of the key building blocks of our system. Extensive trials' results indicate that the system can classify the data traffics dynamically and take the most appropriate routing decisions for each Internet application to maximise users' quality of experience.